Archaeology of agriculture in the Cumbres Calchaquíes (Tucumán, Argentina): new insights into La Ciénega and Tafí Valleys during the first millennium CE - Franco Salvi, Valeria; López Lillo, Jordi A.; Salazar, Julián (Frontiers in Environmental Archaeology, 2025)
This study examines the agricultural and ecological strategies of pre-Hispanic Andean communities, focusing on their innovative practices and land management techniques that fostered complex agrarian systems. It highlights early village settlements in northwestern Argentina, where households thrived for centuries by leveraging local knowledge deeply intertwined with rituals. The research reveals a flexible agricultural system that flourished in the studied valleys, supported by sophisticated social dynamics and advanced agrarian infrastructure. These communities adapted to challenges like uneven terrain, limited water access, and harsh high-altitude climates through a profound understanding of ecology and natural phenomena. The social structure, characterized by autonomous domestic units without centralized hierarchies, enabled efficient management of agricultural plots based on familial knowledge. This autonomy also facilitated coordinated activities like herding and post-harvest maintenance, ultimately enhancing agricultural productivity. The article concludes by emphasizing that applying ancient practices to contemporary sustainability challenges requires a deep understanding of specific cultural and environmental contexts. Rather than relying on generic solutions, it is essential to clearly define and thoroughly study these contexts to ensure their effectiveness and relevance.